Effects of Eugenol on Thermal Autoxidation of Palm Oil - B Purwono; M Muchalal; C Anwar (Indonesian Association of Food Technologists, 1994)
The effects of eugenol on the thermal autoxidation of palm oil were studied in the 40 – 97oC range under atmospheric air system. The antiperoxidative action of eugenol was indexed by measuring peroxide number and methyl esters of fatty acids from palm oil. The eugenol isolated from clove leaf oil exhibited activity as a potential antioxidant for use in mild temperature against thermal autoxidation